Contrasting Patterns of Genetic Isolation Among Diadromous, Landlocked, and Non‐Migratory Gobiid Fish Populations - Jeffery C. F. Chan; Bi Wei Low; Anthony Lau; Frank E. Rheindt; David Dudgeon; Jia Huan Liew (Molecular Ecology, 2026)
Dams can landlock populations of amphidromous fishes that formerly migrated between rivers and seas. However, the genetic consequences of these life‐cycle changes remain unclear. Rhinogobius is a speciose genus of freshwater gobies widely distributed in Asia, including non‐migratory R. duospilus and facultatively amphidromous R. similis . Using genome‐wide SNPs from Hong Kong, southern China, we compared the genetic diversity and structure of R. duospilus (six populations), non‐landlocked R. similis (three populations), and landlocked R. similis (four populations) that had been isolated for 58–106 years. We also used demographic modelling to simulate patterns of gene flow of a panmictic amphidromous population of R. similis fragmented by dam construction 60 years ago. Rhinogobius duospilus populations were deeply divergent, with low genetic diversity; interpopulation differentiation reflected the underlying paleodrainage architecture. In contrast, non‐landlocked R. similis populations were genetically homogenous with high genetic diversity. However, all four landlocked populations of R. similis were highly differentiated, with three populations above tall (> 15 m) dams exhibiting comparable genetic clustering to non‐migratory R. duospilus , although overall genetic diversity remained high. Demographic modelling of a landlocked R. similis population indicated negligible migration into the reservoir and none outward, in accordance with the high levels of genetic divergence among landlocked populations. The effective population size of the original amphidromous population was small (Ne = 81), but the population landlocked above the reservoir for 60 years grew eightfold (Ne = 679). Our modelling suggests that even a limited level of immigration was sufficient to minimize genetic drift and lessen interpopulation divergence.

Graphene-based nanofiltration membranes for bio-effluents downstream processing - Sisi Pu; Hooralain Bushnaq; Hari Kalathil Balakrishnan; James Mcelhinney; Rita F. Pires; Flávia S.C. Rodrigues; Sofia G. Seabra; Ricardo Parreira; Nicholas Low; Monica Faria; Ludovic F. Dumée (Journal of Water Process Engineering, 2026)

Highly Conserved STAT3 Motifs Present in the Neuronal Pomc Enhancer nPE1 are Critical for Maximal Hypothalamic Pomc Expression - Clara E. Hael; Malcolm J. Low; Lucía F. Franchini; Marcelo Rubinstein (Molecular Neurobiology, 2026)

Linking gut, heart and metabolic health through cholesterol conversion by Akkermansia muciniphila - Negin Kazemian; Ramin Karimianghadim; S. Amirhossein Golzan; Nitin; Jackline D.W. Irungu; Geoff B. Coombs; Jonathan Low; Jonathan P. Little; Wesley F. Zandberg; Frank Halperin; Kirk Bergstrom; Avirup Guha; et al. (Chemical Engineering Journal, 2025)

Scale and ecosystem-based management: Navigating mismatches between socio-ecological systems - J. Ellis; E. Macpherson; S. Thrush; K. Fisher; C. Pilditch; E. Jorgensen; J. Low; F. Stephenson; A. Allison; S. Geange; J. Hewitt (Biological Conservation, 2025)

Coupling marine ecosystem state with environmental management and conservation: A risk-based approach - Rebecca V. Gladstone-Gallagher; Judi E. Hewitt; Jasmine M.L. Low; Conrad A. Pilditch; Fabrice Stephenson; Simon F. Thrush; Joanne I. Ellis (Biological Conservation, 2024)

Attention, sentiments and emotions towards emerging climate technologies on Twitter - Finn Müller-Hansen; Tim Repke; Chad M. Baum; Elina Brutschin; Max W. Callaghan; Ramit Debnath; William F. Lamb; Sean Low; Sarah Lück; Cameron Roberts; Benjamin K. Sovacool; Jan C. Minx (Global Environmental Change, 2023)

Toward a network perspective in coastal ecosystem management - Rebecca V. Gladstone-Gallagher; Simon F. Thrush; Jasmine M.L. Low; Conrad A. Pilditch; Joanne I. Ellis; Judi E. Hewitt (Journal of Environmental Management, 2023)

Research trend in Sustainable Development Goals reporting: a systematic literature review - See Mei Low; Dewi Fariha Abdullah; Saleh F. A. Khatib (Environmental Science and Pollution Research, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Coastal flood risk within a peri‑urban area: Sussex Inlet district, SE Australia - E. F. Asbridge; D. Low Choy; B. Mackey; S. Serrao-Neumann; P. Taygfeld; K. Rogers (Natural Hazards, 2022)

Coastal flood risk within a peri-urban area: Sussex Inlet district, SE Australia - E. F. Asbridge; D. Low Choy; B. Mackey; S. Serrao-Neumann; P. Taygfeld; K. Rogers (Natural Hazards, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Betanodavirus : Dissection of the viral life cycle - C‐F Low; B Syarul Nataqain; H‐Y Chee; M Z H Rozaini; M Najiah (Journal of Fish Diseases, 2017)
Progressive research has been recently made in dissecting the molecular biology of Betanodavirus life cycle, the causative pathogen of viral encephalopathy and retinopathy in economic important marine fish species. Establishment of betanodavirus infectious clone allows the manipulation of virus genome for functional genomic study, which elucidates the biological event of the viral life cycle at molecular level. The betanodavirus strategizes its replication by expressing anti‐apoptosis/antinecrotic proteins to maintain the cell viability during early infection. Subsequently utilizes and controls the biological machinery of the infected cells for viral genome replication. Towards the late phase of infection, mass production of capsid protein for virion assembly induces the activation of host apoptosis pathway. It eventually leads to the cell lysis and death, which the lysis of cell contributes to the accomplishment of viral shedding that completes a viral life cycle. The recent efforts to dissect the entire betanodavirus life cycle are currently reviewed.

Current knowledge of metabolomic approach in infectious fish disease studies - C‐F Low; M Z H Rozaini; N Musa; B Syarul Nataqain (Journal of Fish Diseases, 2017)
The approaches of transcriptomic and proteomic have been widely used to study host–pathogen interactions in fish diseases, and this is comparable to the recently emerging application of metabolomic in elucidating disease‐resistant mechanisms in fish that gives new insight into potential therapeutic strategies to improve fish health. Metabolomic is defined as the large‐scale study of all metabolites within an organism and represents the frontline in the ‘omics’ approaches, providing direct information on the metabolic responses and perturbations in metabolic pathways. In this review, the current research in infectious fish diseases using metabolomic approach will be summarized. The metabolomic approach in economically important fish infected with viruses, bacteria and nematodes will also be discussed. The potential of the metabolomic approach for management of these infectious diseases as well as the challenges and the limitations of metabolomic in fish disease studies will be explored. Current review highlights the impacts of metabolomic studies in infectious fish diseases, which proposed the potential of new therapeutic strategies to enhance disease resistance in fish.

Whole-genome sequencing in French Canadians from Quebec - Cécile Low-Kam; David Rhainds; Ken Sin Lo; Sylvie Provost; Ian Mongrain; Anick Dubois; Sylvie Perreault; John F. Robinson; Robert A. Hegele; Marie-Pierre Dubé; Jean-Claude Tardif; Guillaume Lettre (Human Genetics, 2016)

Identification of immune response‐related genes and signalling pathways in spleen of Vibrio parahaemolyticus ‐infected Epinephelus fuscoguttatus (Forskal) by next‐generation sequencing - C‐F Low; N S Mariana; A Maha; H‐Y Chee; M Y Fatimah (Journal of Fish Diseases, 2016)

Non‐immune‐related genes and signalling pathways in spleen of Vibrio parahaemolyticus ‐infected Epinephelus fuscoguttatus (Forskal) - C‐F Low; N S Mariana; A Maha; H‐Y Chee; M Y Fatimah (Journal of Fish Diseases, 2015)

CO2 alters community composition and response to nutrient enrichment of freshwater phytoplankton - Etienne Low-Décarie; Graham Bell; Gregor F. Fussmann (Oecologia, 2015)

Experimental infection of brown‐marbled grouper, E pinephelus fuscoguttatus (Forskal), with V ibrio parahaemolyticus identifies parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain, differentially expressed in resistant grouper - C‐F Low; M Nor Shamsudin; M Abdullah; H‐Y Chee; M Aliyu‐Paiko (Journal of Fish Diseases, 2015)
The mechanisms through which brown‐marbled grouper accomplishes resistance to infection, particularly against Vibrios , are not yet fully understood. In this study, brown‐marbled grouper fingerlings were experimentally infected with Vibrio parahaemolyticus, to identify disease resistance grouper, and the serum proteome profiles were compared between resistant and susceptible candidates, via two‐dimensional gel electrophoresis (2‐ DE ). The results showed that putative parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain proteins were among proteins that significantly overexpressed in the resistant fish as compared to the susceptible group of fish, whereas apolipoprotein E and immunoglobulin light chain proteins were observed to be differentially overexpressed in the susceptible fish. Further analysis by peptide sequencing revealed that the immunoglobulin light chain proteins identified in the resistant and susceptible groups differed in amino acid composition. Taken together, the results demonstrated for the first time that putative parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain are among important proteins participating to effect disease resistance mechanism in fish and were overexpressed to function collectively to resist V. parahaemolyticus infection. Most of these molecules are mediators of immune response.

Putative apolipoprotein A‐I, natural killer cell enhancement factor and lysozyme g are involved in the early immune response of brown‐marbled grouper, Epinephelus fuscoguttatus, Forskal, to Vibrio alginolyticus - C‐F Low; M N Shamsudin; H‐Y Chee; M Aliyu‐Paiko; E S Idrus (Journal of Fish Diseases, 2014)
The gram‐negative bacterium, Vibrio alginolyticus , has frequently been identified as the pathogen responsible for the infectious disease called vibriosis. This disease is one of the major challenges facing brown‐marbled grouper aquaculture, causing fish farmers globally to suffer substantial economic losses. The objective of this study was to investigate the proteins involved in the immune response of brown‐marbled grouper fingerlings during their initial encounter with pathogenic organisms. To achieve this objective, a challenge experiment was performed, in which healthy brown‐marbled grouper fingerlings were divided into two groups. Fish in the treated group were subjected to intraperitoneal injection with an infectious dose of V. alginolyticus suspended in phosphate‐buffered saline ( PBS ), and those in the control group were injected with an equal volume of PBS . Blood samples were collected from a replicate number of fish from both groups at 4 h post‐challenge and analysed for immune response‐related serum proteins via two‐dimensional gel electrophoresis. The results showed that 14 protein spots were altered between the treated and control groups; these protein spots were further analysed to determine the identity of each protein via MALDI ‐ TOF / TOF . Among the altered proteins, three were clearly overexpressed in the treated group compared with the control; these were identified as putative apolipoprotein A‐I, natural killer cell enhancement factor and lysozyme g. Based on these results, these three highly expressed proteins participate in immune response‐related reactions during the initial exposure (4 h) of brown‐marbled grouper fingerling to V. alginolyticus infection.

Imperata cylindrica (Cogongrass) as an Adsorbent for Methylene Blue Dye Removal: Process Optimization - Claire Xin-Hui Su; Tjoon Tow Teng; Abbas F. M. Alkarkhi; Ling Wei Low (Water, Air, & Soil Pollution, 2014)

Safety of combination therapy with milrinone and esmolol for heart protection during percutaneous coronary intervention in acute myocardial infarction - Kian-Keong Poh; Xin Xu; Mark Y. Chan; Chi-Hang Lee; Edgar L. Tay; Adrian F. Low; Koo Hui Chan; Winnie Sia; Liang-Qiu Tang; Huay Cheem Tan; Charles Y. Lui; Vincent Nguyen; et al. (European Journal of Clinical Pharmacology, 2014)

Adapting to climate change in South East Queensland, Australia - Ryan R. J. McAllister; Timothy F. Smith; Catherine E. Lovelock; Darryl Low Choy; Andrew J. Ash; Jan McDonald (Regional Environmental Change, 2014)

Improving cross-sectoral climate change adaptation for coastal settlements: insights from South East Queensland, Australia - S. Serrao-Neumann; F. Crick; B. Harman; M. Sano; O. Sahin; R. van Staden; G. Schuch; S. Baum; D. Low Choy (Regional Environmental Change, 2014)

Chemical Modification of Imperata cylindrica Leaf Powder for Heavy Metal Ion Adsorption - Zhimin Li; Tjoon Tow Teng; Abbas F. M. Alkarkhi; Mohd Rafatullah; Ling Wei Low (Water, Air, & Soil Pollution, 2013)

Molecular Phylogeny and Evolution of the Proteins Encoded by Coleoid (Cuttlefish, Octopus, and Squid) Posterior Venom Glands - Tim Ruder; Kartik Sunagar; Eivind A. B. Undheim; Syed A. Ali; Tak-Cheung Wai; Dolyce H. W. Low; Timothy N. W. Jackson; Glenn F. King; Agostinho Antunes; Bryan G. Fry (Journal of Molecular Evolution, 2013)

Noninvasive diffusive optical imaging of the auditory response to birdsong in the zebra finch - James V. Lee; Edward L. Maclin; Kathy A. Low; Gabriele Gratton; Monica Fabiani; David F. Clayton (Journal of Comparative Physiology A, 2013)

Optimization of the Adsorption Conditions for the Decolorization and COD Reduction of Methylene Blue Aqueous Solution using Low-Cost Adsorbent - Ling Wei Low; Tjoon Tow Teng; Abbas F. M. Alkarkhi; Anees Ahmad; Norhashimah Morad (Water, Air, & Soil Pollution, 2011)

Isolation and identification of hydroxythiohomosildenafil in herbal dietary supplements sold as sexual performance enhancement products - L. Li; M.-Y. Low; F. Aliwarga; J. Teo; X.-W. Ge; Y. Zeng; B.C. Bloodworth; H.-L. Koh (Food Additives & Contaminants: Part A, 2009)

Adeno-associated virus type 2 vectors: transduction and long-term expression in cerebellar Purkinje cells in vivo is mediated by the fibroblast growth factor receptor 1 - Lalitha R. Belur; William F. Kaemmerer; R. Scott McIvor; Walter C. Low (Archives of Virology, 2008)